On the Best Linear Methods of Approximation and the Exact Values of Widths for Some Classes of Analytic Functions in the Weighted Bergman Space - Langarshoev, M. R. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We find the exact values of the series of n-widths for the classes of functions from the Hardy and Bergman spaces whose averaged moduli of continuity are majorized by a given function obeying certain restrictions.